Penggunaan Metode At-Tanzil dalam Membantu Kefasihan Membaca Al-Qur’an di Musholla Al-Muhibbin - sofiatun jannah; uswatun hasanah; syaiful hukama'; fina rahmatika; muliyatul maghfiroh (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2026)
Abstract This study aims to analyze the use of the At-Tanzil method in improving fluency in reading the Qur'an at Musholla Al-Muhibbin, Pamaroh Village, Kadur District, Pamekasan Regency. The At-Tanzil method is recognized as a practical method that accelerates the ability to read the Qur'an through a systematic approach and attention to tajweed principles. This research employed the Participatory Action Research (PAR) approach with data collection techniques including observation, interviews, and documentation. The results show that the implementation of the At-Tanzil method involves several stages, from recognizing vowelized letters, practicing makharijul huruf (points of articulation), to collective tajweed reading sessions. This method has proven effective in enhancing students' fluency and accuracy in reading the Qur'an. Its advantages include a structured learning system, intensive practice, and direct guidance from teachers. However, it also requires skilled educators and regular student attendance. Despite these limitations, the At-Tanzil method remains relevant and effective for teaching Qur'anic reading, especially for beginners. Keywords: At-Tanzil method, fluency in reading the Qur'an.